Cyprus, the United States and the United Nations since 1960 - Coufoudakis, Van (Études helléniques / Hellenic Studies, 1994)
The paper examines aspects of peacekeeping and peacemaking by the United Nations and other regional organizations in the Cyprus problem. The paper focuses on the role of the United States during and after the Cold War. Motivated by strategic interests in the Eastern Mediterranean, the Middle East and as of recent in the Balkans and in Central Asia, the United States has promoted Turkey’s interests in the Cyprus problem, has taken a selective view on the implementation of the unanimous Security Council resolutions on Cyprus, and has failed to promote the rule of law. The paper examines and rejects the Boutros-Ghali “set of ideas” of August 1992, and the so-called confidence building measures. Neither approach would lead to a viable and functional solution of the Cyprus problem, one that would protect the rights of all Cypriots. The paper concludes with suggestions for the future.